BOOK REVIEW. LAS IDEAS EN LA GUERRA. JUSTIFICACIÓN Y CRÍTICA EN LA COLOMBIA CONTEMPORÁNEA - del Prado Higuera, Cristina (Journal of the Spanish Institute for Strategic Studies, 2018)
In his book, Jorge Giraldo Ramírez’s reflections on the Colombian conflict are basedon a close and in-depth understanding of the subject, given that he is not only professorand Dean of the School of Humanities at EAFIT University (Bogota); he hasalso been actively involved in the Historical Commission on the Conflict and Its Victims(CHCV), which was set up as part of a general agreement between the Colombiangovernment and the FARC to end the conflict. He therefore has a very real and comprehensiveoverview of the subject. In addition, the academic works he has publishedin recent years have focused on themes related to contemporary political philosophy,civil wars and criminal economies in South America, where he has provided an enrichingview and approach to the process.